“You do it for the patient”: a qualitative analysis of changes to primary care nurses’ workplace demands and resources during the COVID-19 pandemic in Canada - Sarah Spencer; Lindsay Hedden; Julia Lukewich; Emily Gard Marshall; Maria Mathews; Samina Idrees; Jennifer E. Isenor; Ruth Martin-Misener; Leslie Meredith; Crystal Vaughan; Dana Ryan; Dana Ryan (Frontiers in Health Services)
IntroductionPrimary care in Canada was an essential component of the COVID-19 pandemic response, as well as continued provision of routine care. Yet, primary care settings were inadequately supported during the pandemic, leaving clinicians feeling vulnerable and overwhelmed. Existing pandemic research has focused on the health workforce broadly or those working in acute care settings. Accordingly, we sought to understand the personal and professional experiences of nurses working in primary care settings in Canada during the COVID-19 pandemic to inform future pandemic responses and health workforce planning that account for primary care nurses’ mental and physical needs.MethodsWe conducted semi-structured interviews with licensed and registered practical nurses, registered nurses, and nurse practitioners working in primary care in four Canadian provinces: British Columbia, Newfoundland and Labrador, Nova Scotia, and Ontario. Interviews were recorded, transcribed, and thematically analyzed.ResultsWe interviewed 76 primary care nurses about their pandemic experiences. Using the National Academy of Medicine's systems model of clinician burnout and professional wellbeing, we categorized participants’ experiences according to their job demands and job resources. These data describe how COVID-19 altered primary care nurses’ professional experiences across a variety of areas, often with implications for their wellbeing.DiscussionPrior to the pandemic, primary care nurses could rely on their job resources to protect against the demands they regularly encounter; however, many of these resources were negatively affected by the pandemic. Improved pandemic preparedness, including primary care-specific supports to promote physical and psychological safety, workflow efficiency, worker rest and recovery, and preservation of primary care capacity are needed to uphold primary care nurse wellbeing during a pandemic or other extended health emergencies.